A influência dos determinantes no uso de chupetas e mamadeiras durante o período perinatal e neonatal - Santos, Priscilla Guerra dos (2021)
Introduction: The World Health Organization recommends that breastfeeding be exclusive for the first 6 months and contraindicates the use of artificial teats, as it interferes with breastfeeding practices. The use of artificial nipples has been shown to be associated with several factors, such as: low maternal education, maternal age below 20 years, maternal work outside the home, primiparity, cesarean delivery, low birth weight, among others. Objective: To analyze the influence of health determinants on the use of pacifiers or bottles in the perinatal and neonatal period of babies born in three maternity hospitals in Espírito Santo. Methodology: This is a longitudinal, prospective study carried out with 3429 mothers of babies born alive from August 2019 to March 2020. For data collection, a questionnaire on socioeconomic and maternalinfant characteristics was applied in three moments: interview at the maternity ward and after 7 and 28 days of birth. The relationship between the use of a pacifier or bottle and data related to the mother and the newborn was performed using the chi-square test and the statistical package used was the IBM SPSS 20. Results: Primiparous mothers (OR= 1.424) presented 42% more chance of their children using a pacifier in the neonatal period. Regarding exclusive breastfeeding during the perinatal period (OR=1.817), babies who were not exclusively breastfed were 81% more likely to use a pacifier. Babies born through cesarean delivery (OR=1.651) were 65% more likely to use a bottle in the perinatal period and babies weighing up to 2499 grams (OR=1.566) were 1.5 times more likely to use a bottle during the neonatal period. Conclusion: It can be observed that the use of artificial teats was associated with maternal and newborn factors and characteristics, such as family income, type of delivery, primiparity, gender, baby weight and exclusive breastfeeding. Thus, understanding the determinants associated with the use of pacifiers and bottles in the perinatal and neonatal period allows the adoption of strategies for the prevention and coping with early weaning, both through individual and collective actions.